Household optimism and borrowing - Ari Hyytinen; Hanna Putkuri (Bank of Finland, 2012)
A unique Finnish household-level data from 1994 to 2009 allow us to measure how households financial expectations are related to the sub- sequent outcomes. We use the difference between the two to measure forecast errors and household optimism and link the errors to households borrowing behaviour. We find that households making greatest optimistic forecast errors carry greater levels of debt and are most likely to suffer from excessive debt loads (overindebtedness). They also are less attentive to forecast errors than their pessimistic counterparts when forming their expectations for a subsequent period
URN:NBN:fi:bof-20140807347
Keywords: D21; L20; 330; forecast errors; ex ante optimism; borrowing